Improving The Quality Of Foreign Language Teaching Through The Implementation Of Non-Traditional Methods In Higher Education Institutions - Djumabaeva, Jamila Sharipovna; Jalolova, Shakhnoza Muhamedjanovna; Davidova, Sayyora Sirojiddin qizi; Khaydarova, Dilnoza Doniyor qizi (The journal of contemporary issues in business and government, 2021)
This article discusses the issue of improving the quality of foreign language teaching through the introduction of non-traditional teaching methods in higher education institutions. Quality of education - determines the state and outcome of the educational process in society, as well as the formation and development of professional, domestic and civic competence of the individual in accordance with the needs and requirements of society. The quality of education is assessed by indicators that describe various aspects of the educational activity of the educational institution. These indicators include the content of education, forms and methods of teaching, material and technical base, staffing, etc., which ensure the development of students' competencies. The quality of education in higher education is a multifaceted, multi-level concept related to the indicators, goals and objectives of the education model, as well as specific standards of the education system, educational institutions, curricula and disciplines. This article makes effective use of the latest research on non-traditional teaching methods.